2018
DOI: 10.1007/s11695-018-3228-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Robotic Roux-en-Y Gastric Bypass Provide Outcome Advantages over Standard Laparoscopic Approaches?

Abstract: ObjectiveThe aim was to compare clinical outcomes of patients treated with totally robotic Roux-en-Y gastric bypass (TRRYGB) with those treated with the different laparoscopic Roux-en-Y gastric bypass (LRYGB) techniques.Summary Background DataThe clinical benefit of the robotic approach to bariatric surgery compared to the standard laparoscopic approach is unclear. There are no studies directly comparing outcomes of TRRYGB with different LRYGB techniques.MethodsOutcomes of 578 obese patients who underwent RYGB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Most studies were single-arm studies that reported outcomes only after LRYGB or two-armed studies involving different types of bariatric surgeries. Others were two-armed studies comparing results between Medicaid and non-Medicaid patients [ 23 , 24 ], patients in which a different technique was used to close the gastrojejunostomy [ 30 , 31 , 36 ], or compared private practice versus an academic hospital [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were single-arm studies that reported outcomes only after LRYGB or two-armed studies involving different types of bariatric surgeries. Others were two-armed studies comparing results between Medicaid and non-Medicaid patients [ 23 , 24 ], patients in which a different technique was used to close the gastrojejunostomy [ 30 , 31 , 36 ], or compared private practice versus an academic hospital [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“… ** ***** Li, 2015 [ 42 ] *** . *** ****** Rogula, 2018 [ 31 ] *** ** ** ******* Roy, 2017 [ 36 ] *** ** ** ******* Shah, 2016 [ 28 ] *** ** *** ******** Telem, 2014 [ 29 ] *** . ** ***** Waydia, 2014 [ 35 ] *** .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies referring to RYGB were considered for our analysis, which included 2155 adult patients in total (490 men, 1665 women) 1014. Out of these five studies, one was a prospective randomized trial conducted in the USA comparing robotic with laparoscopic RYGB,14 three were retrospective non-randomized done in the USA comparing again robotic with laparoscopic RYGB,10,11,13 and one was a retrospective non-randomized Swiss study with three treatment arms (robotic, laparoscopic, open) 12…”
Section: Resultsmentioning
confidence: 99%
“…Whether these statements are also valid for RRYGB remains to be shown. While most workgroups opted for a robotic hand-sewn anastomosis [8,11,12,[15][16][17][18][19]33], we kept to the well-established technique using the linear stapler. We decided to use an external linear stapler operated by the assistant.…”
Section: Discussionmentioning
confidence: 99%